2020
DOI: 10.36681/tused.2020.39
|View full text |Cite
|
Sign up to set email alerts
|

Student Achievement on the Concepts of Light and Shadow in Different Assessment Formats: Students Learning Styles and Gender

Abstract: This study was conducted to examine the achievements of students in the concepts of light and shadow measured in different assessment formats according to the learning style and gender. In this study, correlational survey model was used. The sample consisted of 10th grade (16 years) high school students (n=815) from different types of six high schools (public general and vocational) in Turkey who were selected by using stratified random sampling method. The students' achievement was determined using three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The teacher's pedagogical beliefs, which influences their pedagogical reasoning, are essential determinants of the learning outcomes, and therefore necessitates that teachers need to undertake more pedagogical reasoning in the planning of their assessment for learning activities in order to integrate adopt and use appropriate assessment tools and methods (Koh, Chai, & Tsai, 2010;Kreijns, Van Acker, Vermeulen, & Van Buuren, 2013). Furthermore, literature showed that employing different assessment of learning formats (Sari et al, 2020) springs from the belief and knowledge of the learners' different learning styles (Kanli & Ilican, 2020).…”
Section: Pedagogical Beliefmentioning
confidence: 99%
“…The teacher's pedagogical beliefs, which influences their pedagogical reasoning, are essential determinants of the learning outcomes, and therefore necessitates that teachers need to undertake more pedagogical reasoning in the planning of their assessment for learning activities in order to integrate adopt and use appropriate assessment tools and methods (Koh, Chai, & Tsai, 2010;Kreijns, Van Acker, Vermeulen, & Van Buuren, 2013). Furthermore, literature showed that employing different assessment of learning formats (Sari et al, 2020) springs from the belief and knowledge of the learners' different learning styles (Kanli & Ilican, 2020).…”
Section: Pedagogical Beliefmentioning
confidence: 99%